Perception of problems and challenges faced by batik industry woman entrepreneurs in Malaysia. - Mohd Salleh, Naimah; Othman, Mumtazah; Badari, Zainal; Azahari, Shamsul; Bohari, Sharizal
Batik industry has long been established in Malaysia and has remained an important traditional industry till today. Batik is considered a handcraft product and the industry is still very much a labor intensive industry. A lot of effort has been done by the government to improve the potentials of this industry. However, this industry is still having problem in expansion despite demand for batik by local, tourist and exports market. Hence, a study was conducted to identify some of the problems faced by the entrepreneurs. The objective of the study was to determine the profile of the batik entrepreneurs in Terengganu and their perception concerning the industry. A total of 30 respondents were interviewed as well as using of questionnaire. The questionnaire consisted of 4 parts; profile of the entrepreneurs, profile of the company, the perception of the entrepreneur on batik design preferred by customers and the problems in managing their business. Result of the study showed that majority of the batik entrepreneurs were consisted of women and were of ages between 20 to 40 years. Majority of them had completed secondary schooling. In terms of having management experience in the business, only 10 respondents had some experience. Only 14 respondents had undergone some training before starting. Majority put in between 46 to 60 hours of work a week. The respondents that put in more hours of work were found to be more successful in selling more merchandise. In terms of capital investment, most of them invested between RM6000 to RM10000. The design motives most requested by consumers were that of flora and fauna. The types of fabric preferred were of cotton and silk fibers with the fabric construction of satin, organza and chiffon. Problems that were often faced by the entrepreneurs include unstable price of batik, difficulties in getting the loan for capital, lack of business experience, the stiff competition in the market, lack of skilled workers and the high price of raw material as well as difficulties in drying of batik cloth during the rainy season Conclusion: Result of this study implied that there is a need for the entrepreneurs to improve their production in various aspects such as usage of drying machine to overcome problems during the rainy season, training in account management and use of computer for management and design purposes. The entrepreneurs should be consistently aware of their consumer’s needs and demands as well as remain competitive and able to meet fashion changes in order to further improve this batik industry.